Metadata analysis for gut microbiota between indoor and street cats of Malaysia - Tay, Darren Dean; Siew, Shing Wei; Mohd Najib, Razali; Hajar Fauzan, Ahmad (Penerbit UMP, 2021)
With the advancement of sequencing technology, the studies related to the complex nature of microbial communities are possible to be untapped. The goal of this study is to perform a comparison between the composition of bacteria between the gut of Malaysian indoor and street cats. For this research, stool samples of the cats were collected where the genomic DNA were extracted using DNeasy PowerSoil Pro Kit. The extracted DNA were sequenced by targeting the bacterial community using primers from V4 region of 16S rRNA. The raw data were analysed using QIIME2 to obtain the diversity, taxonomy, and differential abundance between the groups. Here, we found that indoor and street cats have similar alpha diversity (p > 0.05), with slight differences between the groups based on the bacterial composition. Likewise, the beta diversity suggest that the two groups are similar to each other. The genus Bifidobacterium, Clostridium, Collinsella, Enterococcus, Cantenibacterium and Lactobacillus from phylum Firmicutes while were found to be more abundant in indoor cats while street cats had more of the phylum Actinobacteria from the genus of Acinetobacter, Blautia, and Olsenella. Hence, we observed whether a cat is kept indoor or is a stray does not significantly cause a shift in their respective microbiota composition.